Predictor Barriers to Self-Care Management in Diabetes Mellitus Clients in Kudus Regency - Lasmini Lasmini; Muhamad Jauhar (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Diabetes Mellitus (DM) is a major health problem both globally and nationally. This is indicated by the increasing prevalence of DM every year. Problems that arise in DM clients include lack of self-management behavior caused by self-efficacy, health literacy, health beliefs and family support. If not handled properly, DM disease has an impact on other disease complications such as: heart, blood vessels, eyes, kidneys, and nerves. This ends in disability or death. This study aims to analyzepredictors of barriers to self-care management in diabetes mellitus clients. The research design uses descriptive correlation with a cross-sectional approach.The research was conducted at the Dawe Community Health Center, Kudus Regency in February 2025. The research sample was 106 respondents using purposive sampling technique.Inclusion criteria in this study were patients suffering from Type 2 DM, patients undergoing DM treatment, Age 18-60 years, able to read and write. While the exclusion criteria in this study were type 2 DM patients who had mental or physical limitations, had complications of diabetic ulcers, and retinopathy. The instrument used in this study was the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire,Diabetes Management Self-Efficacy Scale (DMSES),Health Belief Model Questionnaire(HBMQ), Health Literacy Questionnaire (HLQ). Data analysis using Chi Square test. Research Results Show that Self Efficacy, health beliefs, health literacy, and family support are significantly related to Self-Care Management in diabetes mellitus clients with p-valueof 0.000(p value < 0.05).Further research is expected to develop and provide interventions for inhibiting factors.self care managementin improving self-management skills in diabetes mellitus clients.